2012
DOI: 10.1037/a0025884
|View full text |Cite
|
Sign up to set email alerts
|

Philip G. Zimbardo on his career and the Stanford Prison Experiment's 40th anniversary.

Abstract: name is mentioned often in tandem with the experiment, he has distinguished himself in many other areas within psychology before and after the experiment, beginning with an accomplished early career at New York University in which he took interest in social psychology research on deindividuation. We discussed the Stanford Prison Experiment in the greater context of his varied and illustrious career, including recent pioneering work on heroism, the establishment of The Shyness Clinic at Stanford University, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Zimbardo’s attempt to create a functional simulation of a prison was informed by ex-con Carlo Prescott, yet by Prescott’s (2005) own admission years later, the simulation and results were contrived as the sadistic behaviors of the guards were reproductions of personal experiences Prescott disclosed to the experimenters. In a 2012 interview, Zimbardo described the simulation as “a minimally adequate representation of what I knew was kind of the demonization that went on in prisons” (Drury, Hutchens, Shuttlesworth, & White, 2012, p. 162). Yet it is the “what went on in real prisons” that Zimbardo and colleagues failed to confirm (Fromm, 1973; Haslam & Reicher, 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Zimbardo’s attempt to create a functional simulation of a prison was informed by ex-con Carlo Prescott, yet by Prescott’s (2005) own admission years later, the simulation and results were contrived as the sadistic behaviors of the guards were reproductions of personal experiences Prescott disclosed to the experimenters. In a 2012 interview, Zimbardo described the simulation as “a minimally adequate representation of what I knew was kind of the demonization that went on in prisons” (Drury, Hutchens, Shuttlesworth, & White, 2012, p. 162). Yet it is the “what went on in real prisons” that Zimbardo and colleagues failed to confirm (Fromm, 1973; Haslam & Reicher, 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…For this simulation to be realistic and to have ecological validity, it should have been based on a thorough study of real places of imprisonment. Yet, at the time of the SPE, as Zimbardo admitted, “I knew really nothing about prisons” (Drury, Hutchens, Shuttlesworth, & White, 2012, p. 162). He imagined the SPE almost entirely on the basis of the testimonies of the paid prison consultant Carlo Prescott and of the Toyon Hall experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The SPE clearly showed that human nature could be shaped by social circumstances (Drury et al 2012). Therefore, the inevitable relationship between Zimbardo's main argument, the power of situation (Slavich 2009), and the social model of disability becomes much clearer.…”
Section: The Stanford Prison Experiments and The Social Model Of Disabilitymentioning
confidence: 99%